EFFECT OF CORPORATE GOVERNANCE ON FIRM PERFORMANCE - Korir, Alfred C.; Cheruiyot, Prof. Thomas (European Journal of Business and Strategic Management, 2017)
Purpose: This study sought to investigate the effects of corporate governance on firm performance among companies listed in NSE from 2006 to 2015. Methodology:The study adopted a causal study design of the 55 listed firms in Nairobi Stock Exchange; however, the research used a sample of 35 firms. Secondary data was collected from audited annual financial statements. SPSS was used as the main data analysis tool. Both Descriptive and inferential statistics methods were applied to analyze the data. Results:The study found that board independence had a positive and significant relationship with firm performance measured as return on assets and return on equity. The study also found out that board size had a negative and significant relationship with firm performance. Further the study found out there was a positive and significant relationship between CEO duality and firm performance .The study also found positive and significant relationship between board tenure and firm performance .The study found a positive and significant relationship between multiple directorship and firm performance. Policy recommendation:The study concluded that companies should adopt policies that enhance board independence, CEO Duality and multiple directorships as they improve firm performance however there is need for listed companies to match their board size and board tenure with companies' specific needs.